IgM, IgG, and IgA synthesis in vitro in persons suffering from yersinia arthritis and in patients with ankylosing spondylitis. Issue 2 (April 1984) - Vuento, R; Eskola, J; Leino, R; Koskimies, S; Viander, M
Abstract : In ankylosing spondylitis (AS) and in yersinia arthritis the main findings in serum immunoglobulin (Ig) studies have been raised IgA in AS and a high anti-yersinia IgA and IgG response and the persistence of IgA class antibodies in yersinia arthritis. In order to study predisposition to high IgA response in AS and yersinia arthritis we measured the in-vitro Ig production in patients with AS and in persons who have once had yersinia arthritis, and we compared it with the Ig production in persons who have had yersiniosis but recovered without getting arthritis and with that in healthy controls. IgA secretion by peripheral blood lymphocytes stimulated by pokeweed mitogen was the same in all 4 groups, and no signs of higher IgA production in AS patients could be found. In AS patients lymphocyte activation by whole yersinia bacteria resulted in higher total IgG production than in healthy controls. The total number of plaque-forming cells in yersinia-stimulated cultures was significantly higher in persons who have had yersiniosis without arthritis than in persons who have suffered from yersinia arthritis or in persons in other groups. AS patients had low IgM production, which reverted to normal when hydrocortisone was added to the culture. The in-vitro Ig production in general did not correlate with the presence of the HLA B27 antigen but rather with the clinical history of the subjects studied.